2022
DOI: 10.1108/tpm-05-2022-0037
|View full text |Cite
|
Sign up to set email alerts
|

Linking shared leadership with pharmaceutical team sales performance in Pakistan: a dual mediation model

Abstract: Purpose The pharmaceutical retail industry faces leadership challenges, emphasizing the importance of a mechanism to support sales managers. This paper aims to demonstrate how shared leadership (SL) might improve team performance (TP), with knowledge sharing (KS) and psychological safety (PS) serving as dual mediation effects. Design/methodology/approach The authors used social learning theory (SLT) to support their hypotheses. Using a purposive sampling technique, 440 respondents (65 leaders and 375 team me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 55 publications
(113 reference statements)
0
11
0
Order By: Relevance
“…Following the above procedure, we employed a second aggregation test, depicting that teams differ based on the team members association. The intraclass correlation coefficients (ICC) derivation was employed to achieve this (Bliese and Halverson, 1998;Sabir et al, 2022). That consists of two categories, ICC[1] and ICC [2], and is based on the one-way ANOVA method.…”
Section: Data Aggregation Test Resultsmentioning
confidence: 99%
“…Following the above procedure, we employed a second aggregation test, depicting that teams differ based on the team members association. The intraclass correlation coefficients (ICC) derivation was employed to achieve this (Bliese and Halverson, 1998;Sabir et al, 2022). That consists of two categories, ICC[1] and ICC [2], and is based on the one-way ANOVA method.…”
Section: Data Aggregation Test Resultsmentioning
confidence: 99%
“…Many studies have found a significant impact of SL on TP (Scott-Young et al, 2019;Han et al, 2021;Hsu, Li, & Sun, 2017;Zhu et al, 2018;Hans & Gupta, 2018;Saber, Shoukat, Shah, Selem, & Shaukat, 2022); however, the association between SL and TP can be established through IC. Two studies explored the mediating role of IC between knowledge-sharing activities and financial performance (Wang, Wang, & Liang, 2014) and between knowledgesharing and organizational performance (Iqbal et al, 2019).…”
Section: Mediating Role Of Intellectual Capitalmentioning
confidence: 99%
“…Due to the nature of the PLS-SEM prediction orientation, new estimation techniques have been developed (Dash and Paul, 2021). PLS-SEM is a suitable approach that may be applied in a variety of industries, including healthcare, marketing, tourism and banking (Sabir et al, 2022;Selem et al, 2023;Shoukat et al, 2023a). Moreover, previous researchers in the business field have widely embraced PLS-based analysis due to its statistical robustness and ability to assess proposed relationships while estimating the suggested model (Becker et al, 2023;Hair et al, 2019).…”
Section: Analytics Strategymentioning
confidence: 99%
“…Organizational performance (OP) is pivotal in the contemporary business era (Sabir et al , 2022). Subsequently, most studies have been conducted on factors enhancing OP, like knowledge sharing (Ali et al , 2019) and employee motivation (Kalogiannidis, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation